Hubungan Circadian Rhytme Sleep Disorders Dengan Motivasi Kerja Perawat Di Rumah Sakit Moewardi Surakarta - Firdausi, Rieh, Arief Wahyudi Jadmiko, S. Kep., Ns., M. Kep (2016)
ABSTRACT By: Rieh Firdausi* dan Arief Wahyudi Jadmiko** Nurse job description in shares of emergency installation was patient handling of emergency requiring high intensity and concentration with the situation that uncertain. Trouble of appearance, sleep / Circadian Rhythm Sleep Disorders (CRSD) at nurse affecting at nurse performance specially nurse work motivation. This research was purposed to analyse the correlation of Circadian Rhythm Sleep Disorders (CRSD) with nurse work motivation in Emergency Department RSUD DR. Moewardi Surakarta. This research was a correlation descriptive with the cross sectional approach. The research population was the nurse in the Emergency Department room in of RSUD Dr. Moewardi Surakarta and have a sample account 27 nurses with purposive sampling. The data collecting was using questioner and analyzed was using correlation test. Research result in the form of Rank Spearman correlation of the correlation Circadian Ryhtme Sleep Disorders (CRSD) with nurse work motivation obtained Rs value equal to -0,414 (p-value = 0,032) so H0 refused. Research conclusion the descriptive of Circadian Rhythm Sleep Disorders (CRSD) at nurse in Emergency Department of RSUD Dr. Moewardi Surakarta mostly do not experience of Circadian Rhythm Sleep Disorders (CRSD) (56%), the descriptive of work motivation nurse in Emergency Department of RSUD Dr. Moewardi Surakarta mostly lower equal to 14 respondents (52%), and there were correlation of Circadian Rhythm Sleep Disorders (CRSD) with nurse work motivation in Emergency Department RSUD DR. Moewardi Surakarta. Keywords: Emergency Department, Circadian Rhythm Sleep Disorders, motivation,nurse.